Remote sensing and GIS application in best harvest management planning in Sultan Idris Shah Forestry Education Centre (SISFEC), UPM - Kamarudin, Norizah; Ismail, Mohd Hasmadi; Misnah, E. O. (IOP Publishing, 2013)
This study was carried out in UPM's field centre for education and research. First harvested in the 1960's, this secondary lowland dipterocarp forest should through the second harvest rotation. At the age of 50 years, the timber quality and revenue might decreases. The trees are also a risk to students, researchers and publics. Maintaining the ecosystem sustainability for the continual purpose of education and research, harvesting operation must be commenced by best harvest planning management. Respecting to this study, the application of remotely sensed imagery with the integration of available maps and associated databases have been used. Initially, the interactive feature of SISFEC have been developed in digital terrain model (DTM) identifying the physical and cadastral land classifications information. Several criteria derived from the DTM have been buffered subjected to harvesting practice and mitigation measures for sustainable timber harvesting operation. Eventually, the suitable harvest zones have been determined with total 677.7 ha and 4 km of new extraction road was proposed connecting to the centre of harvesting operation area. Overall, this study has been conducted in respecting the main purpose of this forest. Balance between the sustainability of the ecosystem and development needs of forest and communities are taken into consideration in strategic planning which is vital for continual usage.